Enterprise resource planning business case considerations : an analysis of Small to Medium-Sized Enterprises in developing countries - Mukwasi, Carrington M (Department of Information Systems, 2014)
Small and Medium-Sized Enterprises (SMEs) are implementing Enterprise Resource Planning (ERP) systems because they promise significant benefits. However, the majority of ERP deployments rarely meet user expectations and often do not yield expected benefits. As a result, the failure rate of ERP implementations at SMEs is estimated to be between 40 and 60 percent. This high rate of failure, together with the resultant impact on SMEs and the consequences for national development is a cause for concern. In order to address this concern, this study aims to explore how SMEs develop their business cases, as well as how the benefits, risks and costs of ERP systems are realised in SMEs. Companies need a clear vision and convincing reasons when they adopt ERP systems. The study used the qualitative research method. Cases from South Africa and Zimbabwe were investigated in a cross-sectional study. Data was collected through semi-structured interviews and analysed using elements of thematic data analysis, grounded theory, and a general inductive approach to analysis. The Design Reality Gap Model formed a theoretical base and was used as lens for data collection and analysis.